2013
DOI: 10.1086/671712
|View full text |Cite
|
Sign up to set email alerts
|

Paying the Piper: The High Cost of Funerals in South Africa

Abstract: We analyze funeral arrangements following the deaths of 3,751 people who died between January 2003 and December 2005 in the Africa Centre Demographic Surveillance Area. We find that, on average, households spend the equivalent of a year's income for an adult's funeral, measured at median per capita African (Black) income. Approximately one-quarter of all individuals had some form of insurance, which helped surviving household members defray some fraction of funeral expenses. However, an equal fraction of house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…The other interaction results in Table 5 for the poor are incompatible with herding behavior, suggesting that funeral spending is indeed positional and that the poor feel the greatest pressure to compete. These results are consistent with evidence showing that the poor spending up to several year's income to bury an important member in South Africa (Case et al, 2008) and Ghana (Economist, 2007).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The other interaction results in Table 5 for the poor are incompatible with herding behavior, suggesting that funeral spending is indeed positional and that the poor feel the greatest pressure to compete. These results are consistent with evidence showing that the poor spending up to several year's income to bury an important member in South Africa (Case et al, 2008) and Ghana (Economist, 2007).…”
Section: Resultssupporting
confidence: 90%
“…For example, Case et al (2008) observe that South African households spend the equivalent of one year's income to bury deceased household members while The Economist (2007) reports on "splendid" funerals in Ghana, where the typical burial costs between $2000 and $3500 despite 79% of the population living on less than $2 per day; in each case, lavish spending is intended to indicate the social status of the deceased and the "quality" of the mourning family. In a similar fashion, Anderson (2007) provides evidence that high bride prices and dowries are used to attract socially desirable marital partners for one's children.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated significant conspicuous spending among the lowincome and racial minorities (e.g., Charles et al 2009;Harriger 2010) in developed countries as well as among the poor in developing countries (Banerjee and Duflo 2011;Anderson 2003;Case et al 2013;Guillen-Royo 2011;Jin et al 2011;Linssen et al 2011). Recent evidence from South Asia corroborates the same.…”
Section: Relationship In An Emerging Economy: Case Of Indiamentioning
confidence: 87%
“…Despite the theoretical attention it has received, much of the empirical work examining the relationship between income inequality and conspicuous consumption has focused on developed economies (e.g., Charles et al 2009;Harriger 2010), with some notable exceptions (e.g., Case et al 2013;Fafchamps and Shilpi 2008;GuillenRoyo 2011). We extend this literature by examining the impact of state-level income inequality on conspicuous consumption behavior at the household level in India, an emerging economy, using data from the 2005 India Human Development Survey (IHDS).…”
mentioning
confidence: 99%
“…For example, Bähre (2007) found that groups of Xhosa migrants in Cape Town relied on burial societies to ensure 'proper' burial in their homeland in the Eastern Cape (Bähre, 2007). A 'proper' burial is typically associated with following precise customs of individual communities, including entertaining friends and family attending the funeral for as long as they choose to stay and assisting the family of the deceased (Case et al, 2008;Roth, 1999), and it marks the strength of ties between the deceased person's family and the surrounding community. While formal insurance products pursue profit above all else (Collair, 1992), burial societies integrate cultural and religious values into their structure (Kritzinger, 1996).…”
Section: Burial Societies In Poor African Communitiesmentioning
confidence: 99%